B lymphocytes contribute to stromal reaction in pancreatic ductal adenocarcinoma. (1st January 2020) - Minici, Claudia; Rigamonti, Elena; Lanzillotta, Marco; Monno, Antonella; Rovati, Lucrezia; Maehara, Takashi; Kaneko, Naoki; Deshpande, Vikram; Protti, Maria Pia; De Monte, Lucia; Scielzo, Cristina; Crippa, Stefano; et al.
ABSTRACT: Pancreatic ductal adenocarcinoma (PDAC) is characterized by a prominent stromal reaction that has been variably implicated in both tumor growth and tumor suppression. B-lymphocytes have been recently implicated in PDAC progression but their contribution to the characteristic stromal desmoplasia has never been assessed before. In the present work, we aimed to verify whether B-lymphocytes contribute to stromal cell activation in PDAC. CD19 + B-lymphocytes purified from peripheral blood of patients with PDAC were cultivated in the presence of human pancreatic fibroblasts and cancer-associated fibroblasts. Released pro-fibrotic soluble factors and collagen production were assessed by ELISA and Luminex assays. Quantitative RT-PCR was used to assess fibroblast activation in the presence of B cells. The expression of selected pro-fibrotic and inflammatory molecules was confirmed on PDAC tissue sections by multi-color immunofluorescence studies. We herein demonstrate that B-cells from PDAC patients (i) produce the pro-fibrotic molecule PDGF-B and stimulate collagen production by fibroblasts; (ii) express enzymes implicated in extracellular matrix remodeling including LOXL2; and (iii) produce the chemotactic factors CCL-4, CCL-5, and CCL-11. In addition we demonstrate that circulating plasmablasts are expanded in the peripheral blood of patients with PDAC, stimulate collagen production by fibroblasts, and infiltrate pancreatic lesions. Our results indicate that PDAC is characterized by perturbations of the B-cell compartment with expansion of B-lymphocyte subsets that directly contribute to the stromal reaction observed at disease site. These findings provide an additional rationale for modulating B-cell activity in patients with pancreatic cancer.